Postcolonial control of Fiji soccer and the return of subjugated knowledges: From the 1970s to the 2010s - James, Kieran E.; Tuidraki, Henry D.; Tanzil, Sheikh Ali (Frontiers in Sports and Active Living, 2022)
The Indo-Fijian community of Fiji (i.e., Indians of South Asian descent) has emerged as the effective custodians of the sport of soccer in Fiji. This article explores the status of ex-players of both Indigenous Fijian and Indo-Fijian descent, drawing upon a set of interviews conducted by the first-mentioned author with eight ex-players in 2014-15. When looking at Indo-Fijian control and hegemony, a balanced picture is presented where the positive contributions of Indo-Fijians, both those based in Fiji and in the West, are acknowledged, while the alleged racial or ethnic feeling in the sport is also assessed. The article looks at the prospects of ex-players moving into administration or coaching post-retirement and the ex-player self-help and support organization Nadi Legends Football Club.